Исследование влияния диаметра сатуратора сахарного производства на поглощение диоксида углерода - Ющук, Инна Васильевна; Овчарук, Владимир Алексеевич; Вовкодав (Обизюк), Наталья Ивановна; Метлев, Сергей Геннадьевич (My University, 2013)
Работа посвящена исследованию влияния размеров оборудования для сатурации в процессе очистки диффузионного сока в сахарном производстве. Разработана математическая модель и параметрические схемы для расчета процесса карбонизации. Установлено, что теоретический размер сатуратора меньше тех аппаратов, которые используются на сахарных заводах. Насыщение диоксидом углерода сатурационного газа негативно влияет на коэффициент его использования. The main task of cleaning of the crude juice by lime and kiln gas – the maximum possible removal of various nonsugar components and receive deposit with high sedimentation and filtration performance. One radical methods to improve the filtration-sedimentation properties of deposit – before carbonation treatment. Therefore, in industrial practice, especially in foreign countries, were spread purification and where to get sludge with good sedimentation, filtration properties used predefecosaturation or previous defecation in combination with predefecosaturation. As a result of macromolecular substances and substance coagulated colloidal dispersion with simultaneous dehydration and adsorbed on the surface of the formed crystals of calcium carbonate. The Department of Computer Science (NUFT, Kyiv) work on optimization calculation process equipment intended for the absorption of carbon dioxide with calcium hydroxide to neutralize cleansing crude juice in sugar production. For this purpose was developed a mathematical model calculation process carbonation. The first carbonation of calcium carbonate with the forming of deposit required for its isolation sedimentation and filtration properties. Resulted in a determination that the theoretical size saturator lower than those devices that are used in the sugar factories and varies from 2,5 to 2,1 meters with increasing content of carbon dioxide gas in carbonation. Saturation with carbon dioxide gas carbonation negative impact on rate of its use. With the increase of CO2 in the gas twice the efficiency of its use is reduced by 25%.
Keywords: сахарное производство; оптимизация расчета; очистка диффузионного сока; purifying crude juice; sugar production; optimization of calculation; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки